2018
DOI: 10.1039/c7ob02758c
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of a hybrid framework of indanone and chromane: total synthesis of a homoisoflavanoid, brazilane

Abstract: A chemical backbone of tetracyclic homoisoflavanoid natural products such as brazilin inspired us to design a new chemical scaffold, 6a,11b-dihydroindeno[2,1-c]chromen-7(6H)-one, which is a hybrid structure of indanone and chromane. Pd-catalyzed Suzuki-Miyaura cross-coupling of 4-chloro-2H-chromene-3-carbaldehydes with (hetero)aryl boronic acids was employed as a means to introduce a wide variety of (hetero)aryl groups as the D ring and intramolecular Friedel-Crafts acylation was utilized to construct the C ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…However, NMR analysis of the chromatographically isolated major product revealed that desired product 5 was contaminated with one or more minor impurities. Nevertheless, a one-pot triple O-demethylation of 5 with excess BBr 3 in CH 2 Cl 2 furnished 6 (the thia analogue of the natural product brazilane 11 ), which was significantly purer than 5, although traces of impurity (<5%) still remained with 5.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, NMR analysis of the chromatographically isolated major product revealed that desired product 5 was contaminated with one or more minor impurities. Nevertheless, a one-pot triple O-demethylation of 5 with excess BBr 3 in CH 2 Cl 2 furnished 6 (the thia analogue of the natural product brazilane 11 ), which was significantly purer than 5, although traces of impurity (<5%) still remained with 5.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is achieved through an intramolecular Friedel–Crafts acylation, followed by reduction, resulting in the formation of the brazilane ( 12 ) scaffold (Scheme 4). 60…”
Section: Syntheses Of Brazilin-type Homoisoflavonoidsmentioning
confidence: 99%
“…The molecular formula of brazilin is C 16 H 14 O 5 , which is the main active component in C. sappan. A total of 13 brazilin metabolites (195)(196)(197)(198)(199)(200)(201)(202)(203)(204)(205)(206) have been isolated and identified (Xu et al, 1994;Shu et al, 2007;Hung et al, 2009;Cooksey, 2010;Wang and Liang, 2016;Kim and Kim, 2018). Brizilide is not a component naturally present in hematoxylin itself but rather a newly derived component that emerges during the isolation process from brazilin hematoxylin (Supplementary Figure S1).…”
Section: Brazilinmentioning
confidence: 99%